Analysis of Pink Pigmented Facultative Methylotroph Bacteria from Human Environments - DIANA ELIZABETH WATURANGI; ANDREAS KUSUMA (Microbiology Indonesia, 2008)
The formation of pink biofilm in wet places are usually correlated with chlorine-resistant pink pigmented facultative methylotrophs (PPFM). In this study we investigated the presence of PPFM bacteria through bacterial isolation and detection of mxaF gene from wet places of human-made environments. A total of eighteen PPFM bacterial isolates were recovered from the formation of biofilm bacterial of four test places such as washstands, bathrooms, and potable water supplies. Confirmation of the isolates through biochemical analysis were done using catalase, oxidase and urease tests. Chlorine-resistance-activity was assayed for all of the isolates. Antibiotic resistance were examined for ampicillin (25 μg), tetracycline (30 μg), kanamycin (30 μg), trimethoprim (1.25 μg), and streptomycin (10 μg) using the agar diffusion method. Genomic DNA was subjected to PCR analysis with primers corresponding to the 5’- and 3’- end conserved segments of the mxaF gene. PCR amplification followed by DNA sequencing of 16S rRNA gene were done for some isolates. We recovered 18 isolates of PPFM bacteria. Biochemical analysis indicated that the isolates were positive for catalase, oxidase, and urease activities. Chlorine-resistance-analysis showed the majority of the isolates were resistant to chlorine. Antibiotic resistance assays showed all of the isolates exhibited resistance to trimethoprim but were sensitive to streptomycin, kanamycin, and tetracycline but were variably resistant to ampicilin. PCR detection using specific primers for the mxaF gene gave a positive result for all of the isolates. DNA sequencing of the 16S rRNA gene of two isolates showed that isolate WD10 had a 98% similarity with the mxaF gene from Methylobacterium lusitanum strain MP2 and isolate WK2 had a 98% similarity to the mxaF gene from Afipia felis strain RD1. The formation of pink biofilm of four wet areas in this study were correlated with the presence of chlorine-resistant PPFM bacteria and we confirmed with the presence of the mxaF gene in all of the isolates. This finding needs to be widely publicized since some PPFM bacteria were known as opportunistic pathogens.